P–273 Effects of ovulation induction with GnRH Agonist (GnRHa) on oocyte and embryo quality at the mitochondrial level: A retrospective and experimental study. (6th August 2021) - Basar, M; Olcay, O; Akcay, B; Aydin, S; Neslihan, M; Findikli, N
Abstract: Study question: Does the GnRHa trigger improve oocyte and embryo quality in patients younger than 40, and do mtUPPR have a role? Summary answer: GnRHa trigger improves oocyte nuclear/cytoplasmic maturation, blastocyst utilization and downregulates HSP60 levels and upregulates ATF5 levels compared to hCG trigger. GnRHa trigger suppresses mitochondrial stress. What is known already: hCG has been used for decades to achieve final oocyte maturation and, thereby, correct oocyte retrieval timing in connection with ovarian hyperstimulation protocols. As an alternative to hCG, a GnRH agonist has been used to trigger the endogenous release of LH (and FSH) in a fashion resembling the mid-cycle surge of gonadotrophins. GnRHa is as effective as hCG for the induction of ovulation. It has been very well known that the GnRHa trigger improves oocyte nuclear maturation, embryo quality, and implantation rate, but the underlying mechanism remains unknown. Study design, size, duration: 3054 women younger than 40; oocytes retrieved more than 10 (up to 20) analyzed. Male infertility was excluded. Ovulation triggered either by hCG (n = 1368) or GnRHa (1668). Female mice were divided into three groups as control, hCG-treated and GnRHa-treated group. Superovulation was performed by FSH + hCG or GnRHa. Oocytes were collected 13 hours after hCG/GnRHa injection. ATF5, BiP, and HSP60 levels were analyzed by Western blot. Statistical analysis was performed using Student's t-test. Participants/materials, setting, methods: This study has two parts. i) RCT and ii) Experimental. In the experimental part, three months old female BALB/C mice (25–30 g) were used and divided into three groups (n = 20/group) as control, hCG-treated and GnRHa-treated group. Superovulation was performed by administering an injection of 5 IU FSH (i.p.) and hCG (i.p.) or GnRHa (20 mg/kg) i.m. Oocytes were collected 13 hours after hCG/GnRHa injection. ATF5, BiP, and HSP60 levels were analyzed by Western blot. Main results and the role of chance: The mean age (34.8 vs. 35.2 years), total gonadotropin dose (2176 vs. 2230 IU), and the number of oocytes picked up (14.9 vs. 13.4) were not statistically different among GnRHa and hCG group, respectively. No LH rise or any OHSS was noticed in any groups. Oocyte maturation (79.8% vs. 75.9%), oocyte diameter (as a marker of cytoplasmic maturity) (10198 µm2 and 9474 µm2), fertilization rate (78% vs. 72%), and embryo utilization rate (52% vs. 47.2%) were significantly higher in GnRHa group compared to hCG group, respectively. HSP60 level (activated by mtUPR) was statistically higher in the hCG group compared to the GnRHa group (55% vs. 22%, p < 0.05 respectively). On the other hand, the ATF5 level was significantly higher in the GnRHa group than the hCG group (p < 0.0001). Limitations, reasons for caution: The limitation is that this is a proof-of-concept study to reveal the mechanism of good embryo quality with GnRHa trigger. Wider implications of the findings: This application offers convenience and simplifies the IVF protocol with a better oocyte and embryo quality while reducing Ovarian Hyperstimulation Syndrome (OHSS) risk during IVF care Trial registration number: Not applicable